Perfilman Indonesia Harapan Dan Kenyataan - Budiman, Dwi Aji (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
Previously, the New Order era, many filmmakers complain of the absence of freedom. So they do not make a movie that contains criticism and protest, especially to the govern-ment. Now times have changed. Why do not they make movies critical. Film Indonesia currently exploit as taboo in the social and cultural issues, some social and cultural issues like just lying, do not question the filmmakers those problems. Society was considered problematic and the film only touches the edge themes. Film Indonesia is also a little offensive themes that comment on social life (social commentary) and cultural life (cultural commentary). Yet social and cultural life, as portrayed in the film well, will be able to provide an important contribution to our lives as a nation. Whereas many social phenolmena that have lived followed by a good research will be able to produce a representation of the critical themes and interesting. This is an internal failure of the filmmakers themselves. But there was no denying that there are barriers that are external to the emergence of themes that do not represent a critical public life. Bar-riers were named business interests.Â Keyword: Indonesian film and social representation